Structural changes and influencing factors of human resource allocation for oral health in China - Hong Tan (PLoS ONE, 2025)
Objective In the context of the implementation of the Action Program for a Healthy Dentition in China, to analyze the structural changes and influencing factors of human resource allocation for oral health in China, and to provide a scientific basis for promoting the development of human resources for oral health. Methods Structural change degree analysis (by analyzing the structural change of the components of things to reflect the overall characteristics of the structural change of things) and grey relational analysis (by determining the degree of similarity of the geometric shapes of the reference series and a number of comparison series to determine whether they are closely related) were used to analyze the structural changes and influencing factors of human resources for oral health from 2017 to 2022. Results The age of human resources for oral health in China is mainly 25 ~ 34 years old and 35 ~ 44 years old, with a proportion of 37.30% and 33.30%, respectively, in 2022. The number of years of work experience is mainly 10–19 years, with a proportion of 26.80% in 2022. Educational qualifications are mainly at the college level, with a proportion of 41.20% in 2022. Professional and technical qualifications are mainly at the division/assistant level, with a proportion of 52.30% in 2022. The structural change values for ages 45 ~ 54 and 60 and over are negative overall, with a negative trend. The structural change degree of age reaches 13.60% in 2020, which is a dynamic structural change. The structural change values for work experience of 10 years or more are negative overall, with a negative trend. The structural change values for post-secondary and undergraduate education are positive, with a positive trend. The structural change degree of education fluctuates range from 2.60% to 5.20%. The structural change values for associate and intermediate levels are negative, with a negative trend. The structural change degree of professional and technical qualifications reaches its highest value of 8.80% in 2021. The most influential factor was per capita health expenditure, with a relational of 0.787, followed by per capita disposable income, with a relational of 0.682, and thirdly, per capita GDP, with a relational of 0.667. Conclusion Age of 45 ~ 54 and years of work experience of more than 10 years show an overall negative trend. College and undergraduate education show a positive trend. Per capita health expenditure and per capita disposable income are the main factors influencing the allocation of human resources for oral health. Therefore, the administration should formulate inclined policies to continuously strengthen the introduction and cultivation of human resources for oral health, and all medical institutions should emphasize the academic education and continuing education of dentists, so as to comprehensively promote the development of oral health in China.